Institutions, governance, and the economic performance of protected areas in southern Africa - Chidakel, Alex, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Though wildlife enjoys an economic comparative advantage in dryland areas of southern Africa, public and private investment in this land use varies significantly. This variation exists both between countries with different institutional regimes for wildlife, and between land ownership categories within countries. From an institutional economic perspective, allocation of resources to wildlife-based land uses, and value generated inconsequence, is hypothesized to be in relation to the degree to which rights to own wildlife and responsibility for management are devolved to the scale at which wildlife is produced. Within and between country variation in tenurial and management arrangements therefore presents an opportunity to test predicted relationships with economic efficiency and to explore the implications of institutions on the equity of value distribution. Economic impact analyses, which measure local value in terms of production, income, jobs, and value added, are becoming increasingly common of national parks, though their application to non-public protected areas (PAs) is rare. In this study, impact analysis is applied to both sets of PAs through an ongoing cross-sectional comparison of the economic value of public, private, and communal protected areas of the Greater Kruger Area of South Africa, and of the southern Luangwa Valley in Zambia. It's hypothesized that the value of PAs to which resources are allocated by the state is greater than that of PAs on private and communal land where institutions for wildlife are centralized (Zambia), and vice versa where institutions are devolved (South Africa). Only results for the Luangwa system are here described.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.